Patriotism in Kampak Patik Protests in Ponorogo 1885 - Riyadi, Mohammad Irfan; Faruk, Ahmad; Muzakki, Muhammad Harir; Hasanal, Nurul; Larhzizer, Fouad (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2022)
Dissatisfaction with the policies often leads to protests from the people. It also took place in Ponorogo during the Dutch colonialization in 1885. Indonesian people protested by looting the Dutch Kontroleur Coffee warehouse due to the policy of forced planting and tax tightening. The action is known as Kampak Patik or Patik Robbery. The Dutch Kontroleur deliberately disseminated this negative stigma to impress as criminal behavior against the law. This paper conducts historical defense attempts by examining the value of Patriotism and heroism in the Kampak Patik event. The researchers use three stages of research, namely revealing the background of events, the action events, and the final solution of the action in the form of patriotism values. The approach of this paper is socio-historical with local document data sources (babad), books, and historical data. This paper concludes first, the Dutch policy of forced cultivation and tax tightening had impoverished the citizens in plantations area. Second, the protest was carried out by community leaders, including patih Ponorogo regency, lurah, carik, village staff, and members of Patik village community. Third, there is the value of patriotism, namely the defense of the small people, selfless struggle, sacrifice, and the nature of chivalry. Forth, the Kampak Patik protest had a positive impact on rising coffee commodities and tax reductions.